Market microstructure in emerging and developed markets : price discovery, information flows, and transaction costs - Baker, Kent; Kiymaz, Halil (The Robert W. Kolb series in finance, 2013)
Although the basic function of a marketbringing buyers and sellers togetherhas changed very little over time, how trading occurs within markets has undergone remarkable transformations over the past few decades. This is where market microstructure, which is concerned with how exchange occurs in markets, comes into play. As one of the most dynamic areas of financial economics, market microstructure continues to evolve at a rapid pace. It requires a level of depth and breadth that cannot be found in many of today's best financial resources. That is why H. Kent Baker and Halil Kiymaz have created Market Microstructure in Emerging and Developed Markets. Part of the Robert W. Kolb Series in Finance, this practical guide provides a synthesis of the diverse strands of theoretical, empirical, and experimental literature on the market microstructure of financial markets in both emerging and developed markets. It skillfully blends the contributions of both scholars and practitioners into a single review of some of the most important topics in this area. Each self-contained chapter reinforces the concepts addressed with conclusion summaries and discussion questions of key lessons. Divided into five comprehensive parts, this book not only covers the core issues of market microstructure, but also examines the latest trends and cutting-edge developments in this field. You will become familiar with everything from the market microstructure of various financial marketsequity, bond, futures, and currencyto experimental research on transparency and disclosure, and the impact of information on market participant behavior. Along the way, you will also gain valuable insights into the importance of market design and trading protocols, the dynamic process for determining the price of an asset, and how transaction and timing costs can affect investment returns and execution methods. Stock market efficiency in emerging markets and microstructure related issues regarding new EU emerging markets in Central and Eastern Europe are examined in detail. Market Microstructure in Emerging and Developed Markets offers a fresh look at an intriguing, but complex subject. It is essential reading for anyone who needs a better understanding of how markets work, from seasoned professionals to those aspiring to enter the demanding world of finance.